Indole-3-Carboxylic Acid From the Endophytic Fungus Lasiodiplodia pseudotheobromae LPS-1 as a Synergist Enhancing the Antagonism of Jasmonic Acid Against Blumeria graminis on Wheat - Que, Yawei; Huang, Donghai; Gong, Shuangjun; Zhang, Xuejiang; Yuan, Bin; Xue, Minfeng; Shi, Wenqi; Zeng, Fansong; Liu, Meilin; Chen, Tingting; Yu, Dazhao; Yan, Xia; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The discovery of natural bioactive compounds from endophytes or medicinal plants against plant diseases is an attractive option for reducing the use of chemical fungicides. In this study, three compounds, indole-3-carbaldehyde, indole-3-carboxylic acid (3-ICA) and jasmonic acid (JA), were isolated from the EtOAc extract of the culture filtrate of the endophytic fungus Lasiodiplodia pseudotheobromae LPS-1, which was previously isolated from the medicinal plant, Ilex cornuta. Some experiments were conducted to further determine the antifungal activity of these compounds on wheat powdery mildew. The results showed that JA was much more bioactive than indole-3-carbaldehyde and 3-ICA against Blumeria graminis, and the disease severity caused by B. graminis decreased significantly with the concentration increase of JA treatment. The assay of the interaction of 3-ICA and JA indicated that there was a significant synergistic effect between the two compounds on B. graminis in each of the ratios of 3-ICA to JA (3-ICA:JA) ranged from 1:9 to 9:1. When the compound ratio of 3-ICA to JA was 2:8, the synergistic coefficient was the highest as 22.95. Meanwhile, a histological investigation indicated that, under the treatment of JA at 500 μg/ml or 3-ICA:JA (2:8) at 40 μg/ml, the appressorium development and haustorium formation of B. graminis were significantly inhibited. Taken together, we concluded that JA plays an important role in the infection process of B. graminis, and 3-ICA as a synergist of JA, enhances the antagonism against wheat powdery mildew.